PATH ANALYSIS APPROACH TO ASSESS THE COMPENSATORY IMPACT OF YIELD ATTRIBUTES ON PEARL MILLET GRAIN YIELD IN SEMI-ARID AND ARID AREAS OF PUNJAB, PAKISTAN - A. Ullah; A. Ahmad; T. Khaliq; J. Akhtar; G. Hoogenboom (Journal of Animal and Plant Sciences, 2019)
Yield gaps in agronomic crops are associated with grain number and per unit grain weight. These yield contributing components are interrelated and have compensatory effects on yield. Path coefficient analysis quantifies the direct influence of one yield component upon the other and allows for the separation of correlation coefficients into direct and indirect component effects with respect to various management options. Pearl millet fields with differing planting times (3rd week of June, 1st week of July, 3rd week of July, 1st week of August), with intra-row spacing (10 cm, 15 cm, 20 cm) and nitrogen rate (0, 150, 200, 250 kg ha-1) in semi-arid (Faisalabad) and arid (Layyah) areas of Punjab, Pakistan were used during 2015-16 to examine relationships between yield and yield contributing components via Pearson correlation and path analysis. Correlations of kernels panicle-1 and kernel weight panicle-1 to pearl millet yield were more positive and had strong significance (P≤ 0.001) at both locations. Direct effects of panicle m-2 and kernel weight panicle-1 on grain yield were found at both locations, however, indirect effects of kernels panicle-1 on millet yield via kernel weight were higher at Faisalabad than Layyah (0.63). Kernels per panicle and kernel weight were positively associated with grain yield of pearl millet at both locations. Row spacing, and nitrogen regimes had higher indirect effects of kernels panicle-1 on millet yield via kernel weight than planting time study. Similarly, kernel weight panicle-1 showed higher yield compensation with intra row spacing and nitrogen variation than with planting time and row spacing changes. In conclusion, plant population per unit area and kernel grain weight are the important yield compensation indicators in pearl millet crop under optimum management options.
Keywords: yield compensation; correlation; path analysis; pearl millet